Transurethral Resection of Prostate and Blood loss: Efficacy of Dutasteride in reducing perioperative blood loss. - Shakeel Haseeb Uddin Siddique; Khalid, Salman El; Mithani, Muhammad Shoaib; Mahmood, Abdul Wasay; Anis Khan, Shariq; Yousuf, Fakhir (International Journal of Endorsing Health Science Research, 2021)
Background: Benign Prostatic Hyperplasia (BPH) is the most common urological cause of urinary obstruction, affecting men above 50 years of age. Medical therapy used for managing BPH includes various medical regimes, including 5-alpha reductase inhibitors (5ARI), namely Dutasteride and more. The study aimed to evaluate the efficacy of four weeks' prior treatment with dutasteride on per-operative blood loss in patients of BPH undergoing transurethral resection of the prostate. Methodology: A prospective observational study was conducted from January to December 2019 at the Kidney Centre, Karachi, Pakistan. A total of 64 patients were included and divided into two groups. Group A patients were those who had been taking dutasteride (0.5 mg/day) for four weeks or more before surgery, and group B patients were not taking dutasteride drug before surgery. All patients underwent standard TURP, and the intra-operative blood loss was calculated. The collected data was analyzed using SPSS version 22.0. Results: In our study, there was a significantly less hemoglobin drop (1.2 gm vs. 2.2 gm) during prostate surgery in patients using dutasteride than those who were not using dutasteride. Conclusion: This study has revealed that the use of dutasteride four weeks before surgery significantly reduces intra-operative bleeding.